Uncommon mutational profiles of metastatic colorectal cancer detected during routine genotyping using next generation sequencing - Franczak, Claire (Sci Rep, 2019)
RAS genotyping is mandatory to predict anti-EGFR monoclonal antibodies (mAbs) therapy resistance and BRAF genotyping is a relevant prognosis marker in patients with metastatic colorectal cancer. Although the role of hotspot mutations is well defined, the impact of uncommon mutations is still unknown. In this study, we aimed to discuss the potential utility of detecting uncommon RAS and BRAF mutation profiles with next-generation sequencing. A total of 779 FFPE samples from patients with metastatic colorectal cancer with valid NGS results were screened and 22 uncommon mutational profiles of KRAS, NRAS and BRAF genes were selected. In silico prediction of mutation impact was then assessed by 2 predictive scores and a structural protein modelling. Three samples carry a single KRAS non-hotspot mutation, one a single NRAS non-hotspot mutation, four a single BRAF non-hotspot mutation and fourteen carry several mutations. This in silico study shows that some non-hotspot RAS mutations seem to behave like hotspot mutations and warrant further examination to assess whether they should confer a resistance to anti-EGFR mAbs therapy for patients bearing these non-hotspot RAS mutations. For BRAF gene, non-V600E mutations may characterise a novel subtype of mCRC with better prognosis, potentially implying a modification of therapeutic strategy.